2016
DOI: 10.1186/s12885-016-2878-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of the cytotoxicity of an NHE inhibitor: Evidence of mitochondrial alterations, ROS overproduction and DNA damage

Abstract: BackgroundNH exchangers (NHEs) play a crucial role in regulating intra/extracellular pH, which is altered in cancer cells, and are therefore suitable targets to alter cancer cell metabolism in order to inhibit cell survival and proliferation. Among NHE inhibitors, amiloride family members are commonly used in clinical practice as diuretics; we focused on the amiloride HMA, reporting a net cytotoxic effect on a panel of human cancer cell lines; now we aim to provide new insights into the molecular events leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Intracellular ROS levels have been reported to activate the MAPK signalling pathways (40). Imbalances due to either increased ROS production or decreased ROS degradation may cause excessive ROS accumulation, thus damaging to cell structures and compromising cellular functions (41). Our study showed that NAC completely restored the apoptotic mechanism of A549 cells induced by quinalizarin.…”
Section: Discussionsupporting
confidence: 50%
“…Intracellular ROS levels have been reported to activate the MAPK signalling pathways (40). Imbalances due to either increased ROS production or decreased ROS degradation may cause excessive ROS accumulation, thus damaging to cell structures and compromising cellular functions (41). Our study showed that NAC completely restored the apoptotic mechanism of A549 cells induced by quinalizarin.…”
Section: Discussionsupporting
confidence: 50%
“…Small molecule NHE1 inhibitors have therefore been explored as an anticancer approach, alone or in combination treatment schemes 6,31,32,45 . However, evidence from 2D systems has shown that at high concentrations (20-40 µM, and up to 500 µM for amiloride, compare to IC 50 values for NHE1 inhibition, Table 1), some pyrazinoylguanidine-type NHE1 inhibitors exert NHE1-independent cytotoxicity 24,25,28,46 . Furthermore, pyrazinoylguanidine-type inhibitors inhibit several other NHE isoforms than NHE1 and some additionally target the epithelial Na + channel (ENaC) and Na + /Ca 2+ exchangers [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, the long-term effects of pyrazinoylguanidine-type NHE1 inhibitors, which have generally been assumed to be downstream of NHE1 inhibition, include decreased proliferation, reduced metastatic potential and -viability, and sensitization to chemotherapy 32,45,47,48 . There are, however, reports of NHE1-unrelated effects of these compounds, including dysregulation of ER Ca 2+ homeostasis 24 , reactive oxygen species production 25 , urokinase plasminogen activator inhibition 26 , and cell death 27,28 . The present study is the first to use NHE1 CRISPR/Cas9 KO in conjunction with extensive pharmacological analyses, to unequivocally establish the NHE1-independence of these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, off-target effects of HMA in fungal cells could be possible and would be consistent with other reports that demonstrated HMA activity toward G-protein-coupled receptors, such as the adenosine 2A receptor ( Garritsen et al, 1991 ; Gao and Ijzerman, 2000 ; Soudijn et al, 2004 ). The reported anticancer activity of HMA and its analogs stems from their antitumor/metastasis effects due in part to the inhibition of the human urokinase plasminogen protease that functions as a major driver of cell invasiveness ( Kleyman and Cragoe, 1988 ; Aredia et al, 2016 ; Buckley et al, 2018 ). These various biological activities of HMA may be indicative of other targets in fungal cells, possibly in addition to Nhx1 or Nhe1.…”
Section: Discussionmentioning
confidence: 99%